2019
DOI: 10.1186/s12860-019-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Cited2 regulates proliferation and survival in young and old mouse cardiac stem cells

Abstract: Background Cardiac stem cells (CSCs) exhibit age-dependent characteristics. Cited2 has been implicated in the regulation of heart development; however, there is little known about how Cited2 affects CSC aging. Results Cited2 mRNA and protein level was downregulated in aging heart tissue and CSCs. Old (O)-CSCs showed decreased differentiation and proliferation capacities as compared to Young (Y)-CSCs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, Cited2, a protein implicated in glucose metabolism, has been shown to be important for Sca-1+ cardiac stem cell proliferation [ 42 ]. Although the authors did not measure any metabolic parameter, Cited2 deletion in ESCs has been shown to result in aberrant mitochondrial morphology, reduced glucose oxidation, increased glycolysis, and defective differentiation [ 43 ].…”
Section: Metabolism At the Heart Of Stem Cellsmentioning
confidence: 99%
“…Recently, Cited2, a protein implicated in glucose metabolism, has been shown to be important for Sca-1+ cardiac stem cell proliferation [ 42 ]. Although the authors did not measure any metabolic parameter, Cited2 deletion in ESCs has been shown to result in aberrant mitochondrial morphology, reduced glucose oxidation, increased glycolysis, and defective differentiation [ 43 ].…”
Section: Metabolism At the Heart Of Stem Cellsmentioning
confidence: 99%
“…Donated stem cells are exposed to ischemic cardiac milieu composed of near anoxia, increased ROS and pro-inflammatory factors that together push massive cell loss upon transplantation. Recent studies have shown metabolism as a critical determinant of stem cell fate regulating various processes such as cell proliferation [ 12 ], survival [ 13 ], and commitment [ 14 ]. Metabolic signaling pathways are sensitive to changes in environmental conditions allowing stem cells to adapt to fluctuating oxygen and nutrient levels [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular metabolism has emerged recently as a regulator of stem cell fate as well as molecular and cellular function [21,22]. Changes in environmental conditions alter energy generation in stem cells leading to a shift from a quiescent to proliferative or differentiated state [23].…”
Section: Discussionmentioning
confidence: 99%